Training loads in typical junior-elite tennis training and competition: implications for transition periods in a high-performance pathway - Perri, T.; Norton, K. I.; Bellenger, C. R.; Murphy, A. P. (International Journal of Performance Analysis in Sport, 2018)
The purpose of this study was to describe the differences in training and competition loads at three distinct development levels in a junior-elite tennis academy. A total of 39 junior-elite tennis players were recruited from three squads; U/12, U/15 and U/18. Metrics of global positioning systems, accelerometer microtechnology and hitting demands were quantified to determine the external load. Ratings of perceived exertion (RPE) were used to quantify internal training and competition loads. Two training sessions and one competition match were quantified. The results showed an increase in training hitting demands as age increased from the U/15-U/18 squad (p < 0.05). Serve loads were greater in competition compared to training across all squads (p < 0.05). Perceptions of exertion were greater in competition for the U/12 males (p < 0.01) with the U/15 males showing higher RPE in training (p < 0.05). No differences in perceptions of exertion were seen between female groups in training however, the U/15 females found competition less demanding than training (p < 0.05). Overall, the findings suggest practitioners be aware that the U/15-U/18 transition involves significant increases in hitting loads.